2019
DOI: 10.1371/journal.pone.0223601
|View full text |Cite
|
Sign up to set email alerts
|

Risk of pneumonia among residents living near goat and poultry farms during 2014-2016

Abstract: In the Netherlands, an association was found between the prevalence of pneumonia and living near goat and poultry farms in 2007–2013. This association then led to regulatory decisions to restrict the building of new goat farms and to reduce emissions of poultry farms. Confirmation of these results, however, is required because the period of previous analyses overlapped a Q-fever epidemic in 2007–2010. To confirm the association, we performed a population-based study during 2014–2016 based on general practition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…A strong body of evidence has shown that proximity to livestock farms can be associated with adverse health effects in humans, and with respiratory outcomes in particular (Baliatsas et al, 2017;Borlée et al, 2017;Kalkowska et al, 2018;Maassen et al, 2016;Post et al, 2019;Van den Berg, 2007;Van der Star et al, 2018;Van Dijk et al, 2016). The current study has some inconclusive results.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…A strong body of evidence has shown that proximity to livestock farms can be associated with adverse health effects in humans, and with respiratory outcomes in particular (Baliatsas et al, 2017;Borlée et al, 2017;Kalkowska et al, 2018;Maassen et al, 2016;Post et al, 2019;Van den Berg, 2007;Van der Star et al, 2018;Van Dijk et al, 2016). The current study has some inconclusive results.…”
Section: Discussionmentioning
confidence: 58%
“…Livestock farms are a source of various emissions, such as particulate matter, endotoxins, and ammonia. Acute infections and chronic illnesses have recently been linked to residents of livestock dense areas (Borlée et al, 2017;Kalkowska et al, 2018;Maassen et al, 2016;Post et al, 2019;Van der Star et al, 2018). Furthermore, a variety of zoonotic pathogens are associated with both livestock farms and human health conditions (Morakinyo et al, 2016;Smit et al, 2012;Uiterwijk et al, 2017;Zomer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of specialized farms in one region often exacerbate environmental issues associated with agriculture, e.g., N deposition in nearby natural areas and increased risk of transmittable animal diseases. High concentrations of aerosols and ammonia in regions with a high density of chicken, goat and pig farms are known to affect human health and increase respiratory problems, e.g., pneumonia symptoms of residents living near goat [44] and chicken [45] farms. The probability of zoonotic infection of humans also increases [46] and has caused severe problems with, for example, Q fever in the Netherlands [45] .…”
Section: Benefits and Challenges Of Specialized Farming Systemsmentioning
confidence: 99%
“…However, not all prior studies in the Netherlands pertaining to poultry farms and CAP found consistent, significant results [ 14 , 21 ]. For goat farms, the association with CAP has been more consistent over a long period, from 2009 to 2016 [ 17 , 22 , 23 ]. However, goat farms emit much lower PM levels than poultry farms, and possible underlying biological mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%